HUBUNGAN SHIFT KERJA MALAM DENGAN TINGKAT KECEMASAN PERAWAT DI RS ADVENT BANDAR LAMPUNG - Simanjuntak , Bidan; Arin_Proborini, Christiana (Jurnal Stethoscope, 2025)
Anxiety is an emotional reaction that causes feelings of discomfort and feelings of danger when anxiety is related to disturbances in social function. Forms of anxiety, including physical, emotional, and behavioral. Signs and symptoms are not the same for everyone, common symptoms are emotional symptoms, physical symptoms, behavioral symptoms and cognitive symptoms. The categories of anxiety are Not anxious, mild, moderate, severe and very severe. The general purpose of this study was to determine the relationship between night shift work and the level of anxiety of nurses at the Adventist Hospital Bandar Lampung. The research design used a descriptive correlational method to describe the relationship between two variables, a total population of 133 people and the sample of research respondents were nurses working at the Adventist Hospital Bandar Lampung against all inpatient nurses as many as 100 respondents. Data processing techniques were analyzed using the chi Square test. The results showed a p value of 0.000 <0.005, with a chi square value of 44,702 concluding that there was a significant relationship between night shift work and anxiety levels at the Adventist Hospital Bandar Lampung. The author suggests recommendations from the results of this study for hospital management to review the night shift operating hours system to properly manage the level of anxiety of nurses at Bandar Lampung Adventist Hospital through a welfare approach that includes the physical and mental aspects of nurses.